Achievements of the K1 & K4 Program with Standard Practices of Pregnancy Services during the Covid-19 Pandemic - Nurul Azizah; Rafhani Rosyidah (Jurnal MIDPRO, 2021)
WHO has designated the Covid-19 (Corona Virus 2019) case as a Pandemic. Covid-19, caused by the coronavirus (SARS-CoV-2), is a new type of respiratory disease (pneumonia) and is contagious. The state has made various efforts to control covid-19, but there are still many infected victims. Pregnant women have changes in their immune system and anatomy, making them susceptible to viral infections. Pregnancy examinations at the hospital will be at risk of transmitting covid-19 to pregnant women, while antenatal care is very important to identify any pregnancy complications. This study aims to identify the K1 and k4 programs' achievements with midwives' practice in standard pregnancy services during the Covid 19 Pandemic, using a questionnaire given to midwives as health service workers. The study design used a cross-sectional with a chi-square statistical test, with 30 midwives as respondents who opened independent practice services during the Covid-19 pandemic. The research instrument used a questionnaire. This study indicates that 70% of midwives have good knowledge but do not implement standard pregnancy care during the pandemic. The analysis results show no relationship between knowledge and standard practice of pregnancy services during the Covid-19 pandemic. Conclusion: Most midwives have good knowledge and do not practice standard pregnancy services during the Covid-19 pandemic. Suggestion. The following research is to identify the achievements of the pregnancy care program during the Covid-19 pandemic.